Music Function of Hadrah Al-Banjari Jamiyyah At-Taqwa Banyusangka in Banyusangka Village, Tanjungbumi District, Bangkalan Regency - Dharmawan, Bagus Santoso; ., trisakti . (APRON Jurnal Pemikiran Seni Pertunjukan, 2024)
Hadrah Al-Banjari Jamiyyah At-Taqwa music is one of the arts that developed in Banyusangka Village, Tanjungbumi District, Bangkalan Regency. This research aims to describe the form of music and explain the function of Hadrah Al-Banjari Jamiyyah At-Taqwa music. This research method uses a descriptive qualitative method with data collection techniques carried out by observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, triangulation of library sources, triangulation of sources, presentation, and data verification. The results of this study found the form and function of Hadrah Al-Banjari music. The form of Hadrah Al-Banjari Jamiyyah At-Taqwa music is played in groups with a percussion ensemble format using tambourine, darbuka, tam and bass instruments, by combining musical elements: rhythm/rhythm, harmony, song form, tempo, expression, and instruments. The functions of Hadrah Al-Banjari Jamiyyah At-Taqwa music for the community are as: means of communication, means of education, means of economy, means of entertainment, means of customs and religious rituals. Keywords: Music Form, Music Function, Hadrah Al-Banjari